2009
DOI: 10.1097/gco.0b013e32832924ba
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxidative stress on female fertility

Abstract: Purpose of review To review the role of oxidative stress in the context of female fertility. Recent findings Oxidative stress is associated with decreased female fertility in animal and in-vitro models, but no studies to date have directly assessed the relationship in women. Exposures associated with oxidative stress and with evidence to influence the timing and maintenance of a viable pregnancy include pregnancy complications (e.g. preeclampsia), extremes of body weight, alcohol, tobacco, and caffeine intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(148 citation statements)
references
References 43 publications
1
120
0
5
Order By: Relevance
“…However, no significant change in malondialdehyde (MDA) concentrations was seen after the consumption of selenium supplements in rats [16]. Beneficial effects of selenium supplementation on improved reproductive outcomes, biomarkers of inflammation, and oxidative stress might be attributed to its inhibitory effect on augmentation of proinflammatory cytokines and reactive oxygen species/reactive nitrogen species [17,18]. Borderline selenium status is high among healthy Iranian women.…”
Section: Affiliationsmentioning
confidence: 99%
“…However, no significant change in malondialdehyde (MDA) concentrations was seen after the consumption of selenium supplements in rats [16]. Beneficial effects of selenium supplementation on improved reproductive outcomes, biomarkers of inflammation, and oxidative stress might be attributed to its inhibitory effect on augmentation of proinflammatory cytokines and reactive oxygen species/reactive nitrogen species [17,18]. Borderline selenium status is high among healthy Iranian women.…”
Section: Affiliationsmentioning
confidence: 99%
“…In addition, oxidative stress and a disrupted antioxidant system are reported to be involved in a variety of pregnancy complications such as preterm labor, fetal growth restriction, preeclampsia and miscarriage Sugino et al, 2007). Numerous studies have also shown that oxidative stress plays a role in the pathophysiology of infertility (Tremellen, 2008;Ruder et al, 2009) and assisted fertility .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, antioxidants promote meiosis-II [108]. The ROS produced by the preovulatory follicle is considered an important inducer of ovulation [109]. Thus, ROS do not always cause adverse effects [110].…”
Section: Relationship Between Progesterone and Oxidative Stress In Rumentioning
confidence: 99%